Higher School and Science: Values and Meanings (To the Question of a Status of the Course “History and Philosophy of Science”) - N. I. Kuznetsova (Высшее образование в России)
The article addresses the actual problems of teaching one of the mandatory training courses included in the program of preparation for the final examination before Thesis defense for the degree of Candidate of Sciences. The immediate pragmatic purpose of the introduction of a new subject “History and philosophy of science” in 2007 was to acquaint graduate students and applicants with the basics of research work, to demonstrate them the norms of professional scientific work. The past years of active teaching have brought a valuable experience that deserves reflection. The advantages and disadvantages of this course, and most importantly – its general cultural meanings – can be discussed in detail on the basis of approved pedagogical practices. Familiarization with historical subjects significantly revises the idea of scientific work as a calm, rhythmic, strictly regulated professional activity. The history of science shows how closely linked the experience of knowledge and the experience of existence. Modern epistemology and philosophy of science are an open arena for collision of opinions, positions, principles and concepts. And this is a great advantage for young people to get acquainted with the methodological pluralism that characterizes the dynamics of scientific research. Today, it is the course “History and Philosophy of Science” that is most adapted to develop students’ independent critical thinking as a “universal competence”.